Women who inject drugs in Russia: stigma as a barrier in access to HIV and drug treatment services. (30th September 2020) - King, E; Alexandrova, O; Batluk, J; Shaboltas, A
Abstract: Background: There are over one million people living with HIV in Russia. People who inject drugs experience major disparities in their susceptibility to the virus and in their access to HIV services. Women who inject drugs (WWID) have been shown to be at heightened susceptibility to HIV, through both unsafe drug use and unprotected sex. Less is known about the social determinants of engagement in care specifically among WWID. Methods: We conducted a qualitative research study in St. Petersburg in order to assess what factors influence engagement in HIV-related and drug rehabilitation services. We conducted in-depth interviews with 20 service providers and 30 WWID from June-November 2018. We recruited providers to represent a range of services, including government clinics, non-governmental organizations, and family services. We recruited WWID through community outreach services. We used thematic analysis and a team-based approach to coding data. Results: A major theme across our data was the stigma and discrimination that WWID experience in their everyday lives and in their interactions with the healthcare system. WWID are subjected to stigmatization related to gender norms about drug use, the capacity to fulfill their roles as mothers, (for some) engagement in sex work, and (for some) HIV-positive serostatus. WWID are often reluctant to seek HIV-related services, including testing and treatment, out of fear of being treated poorly because of their drug use. The omnipresent societal stigma manifests into self-stigmatization and many WWID questioned their deserving of and abilities to seek healthcare services, including drug rehabilitation and HIV-related care. Conclusions: Interventions are needed to address the stigma and discrimination that WWID in Russia experience in families, communities, and health institutions. Additionally, psychosocial interventions may help to address the self-stigmatization that sometimes influences WWID's self-efficacy to seek services.